MEDIA MESSAGES: NIGERIAN NEWSPAPERS AND THEIR IMPACT ON WORLD CANCER DAY - Okonkwo, Chinedu Emmanuel; Nwankwo, Joy Ifeoma (Ayden Journal of Management and Social Sciences, 2024)
Cancer, characterized by the uncontrollable abnormal growth of cells forming tumors, poses a severe threat to global public health, causing significant pain and distress to its victims. This pervasive disease, excluding leukemia, manifests across various bodily systems, impacting the digestive, nervous, and circulatory systems. If left undetected and untreated, these tumors can infiltrate surrounding tissues or metastasize through the bloodstream and lymphatic systems, exacerbating the severity of the condition. The International Agency for Research on Cancer (IARC) underscored the magnitude of this crisis, reporting that one in five individuals worldwide succumbs to cancer during their lifetime. The gravity of the situation becomes evident in the statistics presented by the IARC's 2020 report, revealing that one in eight men and one in eleven women globally face mortality due to cancer-related health challenges. The implications of these findings, as elucidated by Mahesar et al. (2021), extend to the fact that over 50 million people currently live within five years of a prior cancer diagnosis. The report further highlights a staggering estimate of million new cancer cases encountered in 2020, contributing to 10 million cancer-related deaths worldwide. This abstract emphasizes the urgent need for a comprehensive understanding of cancer's prevalence, impact, and societal implications. The global scale of cancer-related morbidity and mortality necessitates concerted efforts in research, prevention, and treatment. By acknowledging the profound effects on individuals and societies, this abstract sets the stage for a deeper exploration of the multifaceted challenges posed by cancer and underscores the imperative for innovative strategies to combat its devastating reach